2016
DOI: 10.1097/md.0000000000004606
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding recurrence in patients with gastrointestinal vascular malformation after thalidomide

Abstract: Thalidomide may be used for the treatment of gastrointestinal vascular malformation (GIVM), but the long-term response and adverse effects are unknown. Aim to study the recurrence rate of GIVM bleeding after thalidomide treatment, the response to treatment, and the adverse effects.This was a retrospective study of 80 patients with GIVM treated with thalidomide between November 2003 and November 2013. Patients received a course of 100 mg/day of thalidomide for 4 months and were followed up for at least 1 year. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Whereas the only randomized controlled trial so far by Ge et al[ 10 ] from China found a response rate of 71.4%, patients with cardiac, pulmonary, hepatic, renal, and other comorbidities were excluded from the study. In a follow-up retrospective study by the same group with 80 patients, the response rate to thalidomide in patients with or without comorbidities was 76.7% and 78% respectively, although this study again excluded patients with severe comorbidities such as cirrhosis and severe cardiac and renal conditions[ 14 ]. Therefore, it is unclear whether these results could be applied to other patient populations with significant comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the only randomized controlled trial so far by Ge et al[ 10 ] from China found a response rate of 71.4%, patients with cardiac, pulmonary, hepatic, renal, and other comorbidities were excluded from the study. In a follow-up retrospective study by the same group with 80 patients, the response rate to thalidomide in patients with or without comorbidities was 76.7% and 78% respectively, although this study again excluded patients with severe comorbidities such as cirrhosis and severe cardiac and renal conditions[ 14 ]. Therefore, it is unclear whether these results could be applied to other patient populations with significant comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In studies involving non-LVAD patient populations, recurrent GIB following discontinuation of thalidomide therapy is well-documented and affects up to 20% of patients (16, 17). However, this has not been previously examined in LVAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…They found a significant reduction in bleeding episodes in the thalidomide group, compared with the control group after a mean follow-up period of 39 months. Similarly, Chen et al[62] reported that a significant reduction in bleeding episodes was confirmed in approximately 80% of the patients who received a course of 100 mg/d of thalidomide for 4 mo during a follow-up period of at least one year. However, previous clinical trials reported high rates of adverse events including fatigue, constipation, peripheral neuropathy, leukopenia and liver toxicity[62,63].…”
Section: Treatmentmentioning
confidence: 92%
“…Similarly, Chen et al[62] reported that a significant reduction in bleeding episodes was confirmed in approximately 80% of the patients who received a course of 100 mg/d of thalidomide for 4 mo during a follow-up period of at least one year. However, previous clinical trials reported high rates of adverse events including fatigue, constipation, peripheral neuropathy, leukopenia and liver toxicity[62,63]. Together with the risk of birth defects associated with the use of thalidomide, these findings suggest that the clinical usefulness of thalidomide is likely to be limited to a small number of patients.…”
Section: Treatmentmentioning
confidence: 92%